ESG disclosure, firm internationalization, and firm financial performance: evidence from Asia-Pacific - Hussain, Waleed; Ong, Tze San; Kamarudin, Fakarudin; Khan, Muhammad Asif; Bács, Zoltán (Centre of Sociological Research, 2024)
Environmental, social and governance (ESG) disclosures maintain a sustainable strategic fit between the organization's goals and its changing environment and have an impact on the firm's ability to attract funds, gain competitiveness, and hence firm's financial performance (FFP). The objective of the present study is to evaluate the impact of environmental, social, and governance disclosures (ESGD) on firm financial performance (FFP), especially emphasizing the moderating role of firm internationalization. The study employed a panel dataset of 697 firms listed in the Asia-Pacific emerging economies from 2013 to 2022. The findings of the fixed effect and robust two-stage least square estimations reflect that the modern pillars of corporate social responsibility – ESGD-significantly and negatively influence FFP; however, the degrees of corporate internationalization (international intensity, geographical extensity) significantly and positively moderate the association between ESGD and FFP. The findings of the current study have several implications for regulatory bodies, practitioners, and administrative decision-making authorities in both government and corporations. We further recommend a course of action where an attempt can be made to encourage international trade that is best aligned with the Sustainable Development Goals.